Immune monitoring of SARS-CoV-2-specific T cell and B cell responses in patients with multiple sclerosis treated with ocrelizumab - Groß-Albenhausen, Elina; Weier, Alicia; Velten, Markus; Heider, Thorsten; Chunder, Rittika; Kuerten, Stefanie (Frontiers in Immunology, 2023)
Introduction Since the development of the coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), there has been significant interest in determining the effectiveness of SARS-CoV-2 vaccines in patients under immunomodulatory or immunosuppressive therapies. The aim of this study was to evaluate the impact of ocrelizumab, a monoclonal anti-CD20 antibody, on SARS-CoV-2-specific T cell and B cell responses in patients with relapsing-remitting multiple sclerosis (RRMS). Methods To this end, peripheral blood mononuclear cells (PBMCs) were isolated from n = 23 patients with RRMS. Of these patients, n = 17 were tested before (time point t0) and one month after (time point t1) their first dose of ocrelizumab. In addition, we studied n = 9 RRMS patients that got infected with SARS-CoV-2 over the course of ocrelizumab therapy (time point t2). PBMCs were also isolated from n = 19 age- and gender-matched healthy controls (HCs) after vaccination or infection with SARS-CoV-2, respectively. Interferon-γ (IFN-γ)/interleukin-2 (IL-2) and granzyme B (GzB)/perforin (PFN) double-color enzyme-linked immunospot (ELISPOT) assays or single-color ELISPOT assays were performed to measure SARS-CoV-2 antigen-specific T cell and B cell responses. Anti-viral antibody titers were quantified in the serum by chemiluminescence immunoassay. Results Our data indicate a significant difference in the SARS-CoV-2 specific IFN-γ (P = 0.0119) and PFN (P = 0.0005) secreting T cell compartment in the MS cohort at t0 compared to HCs. Following the first dose of ocrelizumab treatment, a significant decrease in the number of SARS-CoV-2 spike protein-specific B cells was observed (P = 0.0012). Infection with SARS-CoV-2 in MS patients under ocrelizumab therapy did not significantly alter their existing immune response against the virus. Kaplan-Meier survival analysis suggested that the spike S1 protein-specific immunoglobulin (Ig)G response might be a key parameter for predicting the probability of (re)infection with SARS-CoV-2. Discussion Our results call for a critical discussion regarding appropriate vaccination intervals and potential biomarkers for the prediction of (re)infection with SARS-CoV-2 in patients with MS receiving ocrelizumab. Unique identifier DRKS00029110; URL: http://apps.who.int/trialsearch/.